THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION IN COFFEE SHOPS - Muhammad Iqbal; Putri Azarah; Ghisya Siti Rochmah (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study seeks to identify and evaluate the effect of service quality. and product quality on customer satisfaction, this research was conducted at a coffee shop with a sample size of 90 respondents. Determination of respondents was selected through incidental techniques because respondents were selected by chance, The IBM SPSS 20 (Special Package For Statistical Science) application is used to analyze and process data in terms of validity, reliability, classical assumptions, regression analysis, and tests such as T and F. With the results of the t test, it was found that the service quality variable had a positive and significant effect on customer satisfaction with a t value of t1> ttable value (6.506> 1.662) and a significant value (0.000> 0.05), the impact of the product quality variable on customer satisfaction (5.270> 1.662). Simultaneous testing between service quality and product quality on customer satisfaction is known through the F test obtained from the Fhitung test result of 185.343> F table of 3.10 and a significant value of 0.000 <0.05, Service and product quality have a significant influence on customer satisfaction.